SHP-2 in Lymphocytes' Cytokine and Inhibitory Receptor Signaling - Niogret, Charlène; Birchmeier, Walter; Guarda, Greta (Frontiers in Immunology, 2019)
Somewhat counterintuitively, the tyrosine phosphatase SHP-2 (SH2 domain-containing protein tyrosine phosphatase-2) is crucial for the activation of extracellular signal-regulated kinase (ERK) downstream of various growth factor receptors, thereby exerting essential developmental functions. This phosphatase also deploys proto-oncogenic functions and specific inhibitors have recently been developed. With respect to the immune system, the role of SHP-2 in the signaling of cytokines relevant for myelopoiesis and myeloid malignancies has been intensively studied. The function of this phosphatase downstream of cytokines important for lymphocytes is less understood, though multiple lines of evidence suggest its importance. In addition, SHP-2 has been proposed to mediate the suppressive effects of inhibitory receptors (IRs) that sustain a dysfunctional state in anticancer T cells. Molecules involved in IR signaling are of potential pharmaceutical interest as blockade of these inhibitory circuits leads to remarkable clinical benefit. Here, we discuss the dichotomy in the functions ascribed to SHP-2 downstream of cytokine receptors and IRs, with a focus on T and NK lymphocytes. Further, we highlight the importance of broadening our understanding of SHP-2’s relevance in lymphocytes, an essential step to inform on side effects and unanticipated benefits of its therapeutic blockade.